Food Insecurity in the Academic Community During the COVID-19 Pandemic - Gomes, Jéssica (Curr Dev Nutr, 2021)
OBJECTIVES: To investigate the food insecurity of undergraduate and post-graduation students, administrative staff, and professors during the COVID-19 pandemic. METHODS: This is an observational, cross-sectional study, with data collection from October to December 2020 at the Federal University of Rio Grande do Norte, Brazil. The participants answered an online survey with questions on socioeconomic status, demographics, and food insecurity (Brazilian Food Insecurity Scale). A logistic regression model was constructed to investigate socioeconomic variables associated with food insecurity. RESULTS: Overall, 1327 volunteers participated in the study; 66.5% were undergraduates, 8.5% post-graduation students, 13.5% administrative staff, and 11.5% professors. Undergraduates presented a higher prevalence of African-Americans than the other studied groups (11.4% vs. 5.3% in post-graduation students, 5.0% in administrative servers, 3.9% professors, P = 0.004). 23.2% of the undergraduates presented an income up to the minimum wage vs. 1.8% in post-graduation students, 0.6% in administrative servers, and 0.0% in professors (P < 0.0005). More undergraduates and post-graduation students had more reduced family income during the pandemic than other groups (44.3% and 41.6%, respectively vs. 37.6% in administrative staff and 28.1% in professors, P < 0.0005). Food insecurity was more present in undergraduates (32.1% with mild food insecurity, 11.5% moderate and 4.8% severe), than in the other studied groups (post-graduation students: 25.7% mild, 2.7% moderate and 2.6% severe; administrative servers: 19% mild, 1.7% moderate, 0.0% severe; professors: 9.8% mild, 0.0% moderate or severe; P < 0.0005). Food insecurity was associated with reduction of family income due to the pandemic (OR = 2.14, 95%CI = 1.68–2.74) and belonging to white ethnicity (OR = 0.69, 95%CI = 0.53–0.90). CONCLUSIONS: Undergraduates presented more food insecurity than the other studied groups. Food insecurity was associated with reduction of family income due to the pandemic and belonging to white ethnicity protected against food insecurity in the study population. Data shows the need for urgent public policy implementation directed to the undergraduates to guarantee the human right to adequate feeding, aiming for food security. FUNDING SOURCES: CAPES – Brasil (001) and CNPq (405837/2016-0)